Prospects of Vegetable Oils as Lubricant in Crop Cutter and Harvesting Machines. (2018) - Suhane, Amit; Sarviya, R.M.; Siddiqui, A.R.
Abstract: India is an agriculture based economy with more than half of its people dependent on it as a major source of income or livelihood. It is a challenging task to cater the needs of rising population, growing consumer demands amidst irrational infrastructure available and undisciplined agricultural practices. Use of modern methods and machinery in agriculture services like crop cutting and harvesting etc. has resulted in increased productivity, reduced men power and time engaged. Presently, the machinery has been devised with conventional fuel and lubricants to run and execute the requisite agriculture operations smoothly. Loss of conventional lubricants in to the environment due to mishandling, accidental spillages, leakages etc. pose threat and is a matter of serious concern. Escalating petroleum prices and their depleting reserves further restricts conventional lubricant availability and its compatibility to metallic interactions. Use of vegetable oils and their derivatives being environmental friendly can be better options in long run to replace the harmful oils as lubricant due to their remarkable clean and green inherent technical features. In present article an insight has been made to study and analyse the feasibility of utilizing vegetable oils as a source of lubricants in crop cutter and harvesting machines.